Folk Songs as a Tool for Teaching EVS in the Context of Assam - DEY, TULIKA (THE PRIMARY TEACHER, 2014)
Music can be used to provide an introduction to, and stimulate interest in, subjects across the curriculum. There is a growing need to integrate arts in the education system and this has been repeatedly debated, discussed and recommended as we face the danger of losing our unique cultural identity and it also helps focus a learner’s attention. In this endeavour, in the State of Assam, an exercise was done among a group of students to generate awareness on issues of environmental degradation and ways to tackle these problems through folk songs. They could relate to the cause and effects of the environmental degradation much easily and were sensitised.